Classification of Mandible Defects and Algorithm for Microvascular Reconstruction. Issue 4 (April 2015) - Schultz, Benjamin D.; Sosin, Michael; Nam, Arthur; Mohan, Raja; Zhang, Peter; Khalifian, Saami; Vranis, Neil; Manson, Paul N.; Bojovic, Branko; Rodriguez, Eduardo D.
Abstract : Background: Composite mandibular tissue loss results in significant functional impairment and cosmetic deformity. This study classifies patterns of mandibular composite tissue loss and describes a microvascular treatment algorithm. Methods: A retrospective review of microvascular composite mandibular reconstruction from July of 2005 to April of 2013 by the senior surgeon at the R Adams Cowley Shock Trauma Center and at The Johns Hopkins Hospital yielded 24 patients with a mean follow-up of 17.9 months. Causes of composite mandibular defects included tumors, osteoradionecrosis, trauma, infection, and congenital deformity. Patients with composite tissue loss were classified according to missing subunits. Results: A treatment algorithm based on composite mandibular defects and microvascular reconstruction was developed and used to treat 24 patients. A type 1 defect is a unilateral dentoalveolar defect not crossing the midline and not extending into the angle of the mandible. A type 2 defect is a unilateral defect extending beyond the angle. A type 3 defect is a bilateral defect not involving the angles. A type 4 defect is a bilateral defect with extension into at least one angle. Type 2 defects were the predominant group. Patients had microvascular reconstruction using either fibula flaps ( n = 19) or iliac crest flaps ( n = 5). Complications included infection, partial necrosis, plate fracture, dehiscence, and microvascular thrombosis. Conclusion: This novel classification system and treatment algorithm allows for a consistent and reliable method of addressing composite mandibular defects and focuses on recipient vasculature and donor free flap characteristics. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital content is available in the text.